The digital age, the alternate bridge in the age of global uncertainty (Raíces: Revista de Ciencias Sociales y Políticas, 2021)
The current events that our society lives have marked the future of generations. The new reality imposed a legacy in a short time affecting all the existing communication bridges that with effort and years of work were built. The human being is a changing entity and adaptable to the situation that is presented to him, he will look for a means to solve and satisfy his needs, so the change in his environment is a way of growing ideas that will prolong his stay in his natural habitat. Having access to the media will fill those who possess it with knowledge, but it will also create a long gap that separates those who lack the equipment to obtain it. The following study reflects in a personal way the experiences that are shaping in a transcendental way a future that was not planned and that has caused a global commotion, but that at the local level still struggles to adapt to the margins that have been imposed, to stand firm in the storm.
Keywords: Society; Reality; ideas; knowledge; experiences; needs